Low dose-ethanol modulates toxic effect of iron-overloading in the liver - Beutelspacher, Sven C.; Serbecic, Nermin; Tan, Peng Hong; Mehrabi, Mohammad; Nielsen, Peter; Yamane, Yosuke (Journal of nutritional science and vitaminology, 2004)
The oxidant properties of iron-overload and simultaneous ethanol consumption have received much interest, due to evidence reporting from hereditary hemochromatosis (HC). The full form of this disease is often associated with chronic alcoholism. An additive effect of toxicity of iron and ethanol was assumed. In this study, we examined nutritively iron-loaded wistar rats (n=59) (TMH-Ferrocene) additionally fed with ethanol up to 8% in drinking water for 36 wk. Methods: By reverse-phase HPLC we measured the concentration of ascorbic acid, tocopherole and retinol in serum and liver homogenates as well as transaminases in the serum. Lipid peroxidation was assessed utilizing the ethane-exhalation method. Iron concentration in the liver was measured with the Bathophenanthrolinmethod. Liver histology was performed to investigate the iron deposits and the organ damage (H. E., Azan and Berlin-blue-stainings). Results: 1. Vitamin C: A linear decrease of the concentration of vitamin C in serum and liver was found independent of alcohol and iron uptake. 2. Vitamin E: Animals fed iron and alcohol showed elevated vitamin E concentrations in the serum but not in the liver. 3. Vitamin A: Elevated levels in serum but strongly decreasing levels in liver could be measured. 4. Histology: All iron-fed animals showed massive deposits of iron in the liver. Iron diet caused liver cirrhosis, while an additional administration of ethanol could prevent this. 5. Lipid peroxidation increased in animals fed ethanol and iron, but was significantly lower in animals only receiving an iron diet. Conclusion: Evidence indicates that the additional exposition to ethanol in iron-loaded animals could modulate the organ damage and oxidative stress. The biochemical findings are positively correlated to the histology.
Gesehen am 02.03.2021